2003
DOI: 10.1152/ajpheart.00564.2002
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of heart rate and contractility to myocardial oxygen balance during exercise

Abstract: Berdeaux. Contributions of heart rate and contractility to myocardial oxygen balance during exercise. Am J Physiol Heart Circ Physiol 284: H676-H682, 2003. First published October 24, 2002 10.1152/ajpheart.00564.2002The respective contributions of heart rate (HR) reduction and left ventricular (LV) negative inotropy to the effects of antianginal drugs are debated. Accordingly, eight instrumented dogs were investigated during exercise at spontaneous and paced HR (250 beats/min) after administration of either s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
86
0
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(102 citation statements)
references
References 21 publications
8
86
0
8
Order By: Relevance
“…The serum level of NT-proBNP in the ivabradinepretreated group was significantly lower than that of the control MI group. This is consistent with data obtained by Sarullo et al [52] and could be attributed to HR reduction by ivabradine reduces ventricular wall stress during ischemia [47] .…”
Section: Shireen Sami Mahmoud ; Et Al…supporting
confidence: 93%
See 3 more Smart Citations
“…The serum level of NT-proBNP in the ivabradinepretreated group was significantly lower than that of the control MI group. This is consistent with data obtained by Sarullo et al [52] and could be attributed to HR reduction by ivabradine reduces ventricular wall stress during ischemia [47] .…”
Section: Shireen Sami Mahmoud ; Et Al…supporting
confidence: 93%
“…These results are consistent with that obtained from previous other short-term experimental studies which demonstrated that ivabradine and β-blockers possess complementary and perhaps even additive pharmacological properties linked to their common ability to reduce HR [42,47] . As regard the combined pretreatment with ivabradine and enalapril, the results of the present study demonstrated that ST height and T-wave voltage were not significantly different from either ivabradine or enalapril demonstrating no interaction of the two drugs on these parameters.…”
Section: Shireen Sami Mahmoud ; Et Al…supporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, it seems that the increased length in diastole attained by both drugs only occurs during rest when treated with BAAs, whereas it is present at rest and during exercise in patients treated with ivabradine [32]. Another important aspect is the lowering of blood pressure that is observed with BAAs, whereas ivabradine fails to change blood pressure.…”
Section: Ivabradine Versus Baasmentioning
confidence: 99%